2022
DOI: 10.15562/bmj.v11i1.2986
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between diabetes distress and HbA1C level in type 2 diabetes mellitus therapy patients: a systematic review

Abstract: Introduction: The success of therapy did not follow the increasing number of type 2 diabetes mellitus patients. This systematic review aimed to evaluate the relationship between diabetes distress and HbA1c in type 2 diabetes mellitus patients during therapy. Methods: The authors systematically searched databases (PubMed, Cochrane library, and ScienceDirect) up to January 2021. Articles were screened according to PRISMA 2020 statements. The selection criteria of this study were patients’ characteristics, type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…DD can directly increase the cortisol hormone, which suppresses insulin production leading to an increase in HbA1c. 37 Indirectly, high disease distress can affect self-efficacy, diabetes self-management behaviors, and medication compliance and consequently worsen glycemic control. 36,37 Lack of glycemic control can generate distress, which can affect disease management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DD can directly increase the cortisol hormone, which suppresses insulin production leading to an increase in HbA1c. 37 Indirectly, high disease distress can affect self-efficacy, diabetes self-management behaviors, and medication compliance and consequently worsen glycemic control. 36,37 Lack of glycemic control can generate distress, which can affect disease management.…”
Section: Discussionmentioning
confidence: 99%
“…37 Indirectly, high disease distress can affect self-efficacy, diabetes self-management behaviors, and medication compliance and consequently worsen glycemic control. 36,37 Lack of glycemic control can generate distress, which can affect disease management. 36 The Brief-IPQ revealed that these T2DM patients perceived their condition as chronic with an important impact on life.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 DM is defined as a hyperglycemic syndrome resulting from defects in beta cell insulin secretion, tissue insulin resistance, or both. It has been considered a global health problem, 8 affecting approximately 387 million people in 2013 and will be doubled by 2035 according to the International Diabetes Federation (IDF) estimation. Among several types of DM (type 1 DM, type 2 DM, gestational DM, and specific DM), type 2 DM is the most dominant, accounting for approximately 90% of DM cases worldwide and 97.5% of DM cases in Indonesia.…”
Section: Introductionmentioning
confidence: 99%